2010
DOI: 10.1111/j.1465-3362.2009.00135.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of life quality with alexithymia, temperament and character in male alcohol‐dependent inpatients

Abstract: Among alcohol-dependent men, DIF factor of alexithymia and personality dimensions, particularly HA and NS are associated with impairment of QoL. Direction of this relationship and factors that may mediate this relationship is unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…Although similar research involving the relationship of QOL with personality temperament and character dimensions is rather scarce, these findings are reasonably comparable with a recent study by Evren et al, 17 as they investigated the relationship of life quality with alexithymia, temperament, and character dimensions of personality in alcohol-dependent patients. They found that alexithymia, novelty seeking, and harm avoidance were negatively correlated with QOL scores, whereas reward dependence, self directedness, and cooperativeness were positively correlated with QOL scores.…”
Section: Addictive Disorders and Their Treatmentsupporting
confidence: 88%
“…Although similar research involving the relationship of QOL with personality temperament and character dimensions is rather scarce, these findings are reasonably comparable with a recent study by Evren et al, 17 as they investigated the relationship of life quality with alexithymia, temperament, and character dimensions of personality in alcohol-dependent patients. They found that alexithymia, novelty seeking, and harm avoidance were negatively correlated with QOL scores, whereas reward dependence, self directedness, and cooperativeness were positively correlated with QOL scores.…”
Section: Addictive Disorders and Their Treatmentsupporting
confidence: 88%
“…Researches suggest that NS represents a vulnerability factor for substance abuse in general [33,34], a risk factor for dropping out of treatment [35], associated with craving scores [36–39] and a predictor of relapse in detoxified male alcohol dependents [40]. A recent study revealed that NS might also be related with impairments in mental component of life quality among this population [41]. Furthermore, NS predicts early‐onset alcohol abuse [42] and is associated with the amount of drinking and severity of dependence [43,44].…”
Section: Introductionmentioning
confidence: 99%
“…Researches suggest that NS represents a vulnerability factor for substance abuse in general (6,7), risk factor for dropping out of treatment (8), associated with craving scores (9-12) and a predictor of relapse in detoxified male alcohol dependents (13). A recent study revealed that NS temperament, which is directly related with occurrence, maintenance and relapse of alcohol dependence, might also be related with impairments in mental aspect of life quality (but not physical aspect of life quality) among this population, whereas for other populations, such as schizophrenia patients, this dimension might have a protective role for mental life quality (14).…”
Section: Introductionmentioning
confidence: 85%
“…4-6 weeks after the last day of alcohol use. In this first interview, patients were evaluated with 7 dimension of Temperament and Character Inventory (TCI) and studies concerning these data were published previously (14,20).…”
Section: Subjectsmentioning
confidence: 99%